Comprometimento organizacional e estratégia de gestão de pessoas dos diferentes vínculos empregatícios em projetos de TI - Aidar, Tatiana Malcher (2012)
Projects in the area of information technology (IT) are very common in Brazil to hire professionals with different employment contracts, who are frequently working together on the same project. Among these contract types, the most common forms are first, the use of formal Brazilian labor laws (CLT), and second, the contract as outsourced service providers - which is often motivated by the possibility of reducing the employment taxation costs. . The focus of this study is then the human resources strategies to manage these professionals, who work together but have different employment contracts. Our objective was to analyze the differences of commitment among employees of IT projects hired through the formal contracts (named CLT) and those who were hired through outsourcing. Our choice of method was a case study, with an IT company, where we collected quantitative data with its employees and we qualitative data via interviews with the company s owner.. The employees organizational commitment was measured by a validated instrument developed by Medeiros (1997). Data was collected through a Web site called SurveyMonkey. Then, interviews were conducted with directors of the company management of IT projects, in which we analyzed the HRM policies to identify differences in the employment relationships. A total of 62 valid Responses were analyzed using descriptive statistic techniques. The results showed that the company, in our case, the affective commitment was strongly indicated by both employment contracts, without presenting substantial differences between them. However, some nuance commitment was different for the groups, and are explored in the study. While employees of traditional projects (CLT) had higher affective commitment than other forms of commitment, employees of outsourced projects presented differently than expected, normative commitment with the highest average. When analyzing the HRM policies adopted by the company, we discuss them based on our results and we propose a theoretical model that can be used in organizations to manage IT employees from different employment contracts, based on theoretical findings of the quantitative survey and interviews.